Two Cases of Rectal Xanthoma Presenting as Yellowish to Whitish Lesions during Colonoscopy - Masaya Iwamuro; Takehiro Tanaka; Daisuke Takei; Yuusaku Sugihara; Keita Harada; Sakiko Hiraoka; Yoshiro Kawahara; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
Two cases of rectal xanthomas are described. One case is that of a 56-year-old Japanese man in whom multiple yellowish spots measuring approximately 3 to 5 mm were observed in the rectum during colonoscopy. The other case is that of a 78-year-old Japanese man in whom colonoscopy showed a whitish plaque of 4 mm in diameter in the rectum. Biopsy examinations performed on both patients revealed the deposition of xanthoma cells within the rectal mucosa. Within the gastrointestinal tract, xanthomas most frequently arise in the stomach, whereas the colorectum is rarely affected. Despite this infrequency, the two cases indicate that xanthomas should be recalled when yellowish to whitish lesions are observed in the colorectum.